Conflict and its impact on educational accumulation and enrollment in Colombia: What we can learn from recent IDPs - Kate Wharton; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2011)
Forty years of low-intensity internal armed conflict has made Colombia home to the world's second largest population of Internally Displaced Persons (IDPs). The effect of being directly impacted by conflict on a child's educational accumulation and enrollment is of particular concern because of the critical role that education plays in increasing human capital and productivity. This paper explores the educational accumulation and enrollment gap created by being directly affected by conflict. First, we show that children living in municipality with high conflict have a gap in education enrollment and accumulation. However, this gap is much smaller than the attainment and enrollment gap for those directly affected by the conflict (IDPs). We estimate the education accumulation and enrollment gaps for IDPs in comparison to non-migrants and other migrants respectively. Our results suggest significant education accumulation and enrollment gaps for children of IDPs that widens to over half a year in secondary school. The disparity in effects when we focus on direct exposure to conflict versus living in a municipality with conflict suggests a need to be careful when using the latter to estimate the impact of conflict.
urn:nbn:de:101:1-201109286329
Keywords: I24; O12; O15; J10; 330; educational attainment; school enrollment; Colombia; internal displacement; conflict; Bürgerkrieg; Flüchtlinge; Kinder; Schulbesuch; Bildungsniveau; Kolumbien